Improving cannulation time for extracorporeal life support in refractory cardiac arrest of presumed cardiac cause – Comparison of two percutaneous cannulation techniques in the catheterization laboratory in a center without on-site cardiovascular surgery. (January 2018) - Voicu, Sebastian; Henry, Patrick; Malissin, Isabelle; Jean-Guillaume, Dillinger; Koumoulidis, Anastasios; Magkoutis, Nikos; Yannopoulos, Demetris; Logeart, Damien; Manzo-Silberman, Stéphane; Péron, Nicolas; Deye, Nicolas; Megarbane, Bruno; et al.
Abstract: Background: Cardiac arrest (CA) without return of spontaneous circulation can be treated with veno-arterial extracorporeal membrane oxygenation (vaECMO) implemented surgically or percutaneously. We performed a study assessing time for vaECMO percutaneous cannulation in the catheterization laboratory. Methods: Single-centre retrospective study in a University hospital without on-site cardiovascular surgery, including patients aged >18 receiving vaECMO for out- or in-hospital refractory CA of presumed cardiac cause between 2010 and 2016, cannulated by interventional cardiologists. Cannulation time using anatomic landmarks vessel puncture and conventional wires (first period) was compared with ultrasound guidance puncture and stiff wires (second period). Data are expressed as medians (interquartile range) and percentages. Results: Forty-six patients were included, age 56 (49–62), 34 in the first period. Shockable initial rhythm occurred in 29 (63%), 36 (78%) had ischemic heart disease and 26 (57%) acute myocardial infarction (AMI). Out-of-hospital refractory CA occurred in 27 (59%) patients. Time from out-of-hospital refractory CA to admission was 100 (80–118) min. Cannulation was successful in 42 (91%) patients. Cannulation time was 14 (10–21) min, 17 (12–26) (first) and 8 (6–12) min (second period), p < 0.001. Survival to discharge was 9%. In out-of-hospital versus in-hospital, time from CA to vaECMO was 120 (115–140) versus 82 (58–102) min, p = 0.011, survival was 7% (two patients) versus 11% (two patients), p = 0.35 respectively. All survivors had shockable initial rhythm. Conclusion: In these refractory CA patients with high prevalence of AMI and good feasibility of percutaneous vaECMO in the catheterization laboratory, cannulation time was shorter using ultrasound guidance and stiff wires.